Guiding esophagectomy with intraoperative NIR-II fluorescence video imaging and rapid computation - Feifei Wang; Ian Yu Hong Wong; Haoran Liu; Zhisheng Wu; Claudia Lai Yin Wong; Danyang Xu; Desmond Kwan Kit Chan; Betty Tsz Ting Law; Fion Siu Yin Chan; Liangqiong Qu; Simon Ying Kit Law; Hongjie Dai (Proceedings of the National Academy of Sciences, 2025)
Preclinical shortwave infrared/near-infrared II (SWIR/NIR-II, 1,000 to 3,000 nm) fluorescence imaging has shown superior contrast, resolution, and penetration depth compared to traditional near-infrared I (NIR-I, 700 to 900 nm) imaging, owing to reduced light scattering and tissue autofluorescence. Here, we carried out clinical translation of NIR-II fluorescence imaging to guide esophagectomy through intraoperative video imaging and rapid analysis of blood perfusion in the gastric conduits (GC) of esophageal cancer patients, following intravenous administration of indocyanine green (ICG). Within <1 min, NIR-II video imaging clearly visualized the spatial and temporal blood flow features, and importantly, intraoperative principal component analysis (PCA) of the video revealed distinct perfusion patterns in GC. This led to rapid, subjective decision-making for targeted resection of poorly perfused tissue and informed reconstruction of the GC to reduce the risk of life-threatening anastomotic leakage. This approach enhances surgical precision and improves outcomes by providing operator-independent intraoperative guidance.